1979
DOI: 10.1172/jci109279
|View full text |Cite
|
Sign up to set email alerts
|

The Handling of Immunoreactive Vasopressin by the Isolated Perfused Rat Kidney

Abstract: A B S T R A C T Using the isolated rat kidney perfused with an artificial medium containing glucose as the sole fuel, we studied the renal handling of immunoreactive arginine vasopressin (AVP) and determined the effect of various factors on the ability of the kidney to remove AVP.In control kidneys perfused with AVP at concentrations below 116 uU/ml, the organ clearance of AVP (OCAVP) was 1,145±47 (SE) p1l/min, whereas glomerular filtration rate (GFR) averaged 515±37 ,ul/min. Filtration could thus account for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 29 publications
(22 reference statements)
3
5
0
Order By: Relevance
“…The same approach to our data would lead to a smaller value (approximately 8 min from the data shown on Fig. It is also in agreement with earlier [20] and more recent [5] work using the isolated perfused rabbit [20] or rat [5] kidney. However, the two half-lives derived by Wilson et af.…”
Section: Discussionsupporting
confidence: 91%
“…The same approach to our data would lead to a smaller value (approximately 8 min from the data shown on Fig. It is also in agreement with earlier [20] and more recent [5] work using the isolated perfused rabbit [20] or rat [5] kidney. However, the two half-lives derived by Wilson et af.…”
Section: Discussionsupporting
confidence: 91%
“…This study, utilizing the IPRK, demonstrated that renal CGRP clearance occurs in the filtering kidney but almost ceases with the abolition of filtration. This finding is consistent with the elimination pattern of many other peptides, including parathyroid hormone, glucagon, growth hormone and prolactin (but not insulin or arginine vasopressin) where renal elimination is by intraparenchymal degradation after tubular reabsorption, with little or no active degradation in the glomerular capillary endothelium (Maack 1974;Rabkin & Kitaji 1978, 1983Rabkin et al 1979;Carone & Peterson 1980). Only 25% of total CGRP clearance can be accounted for by CGRP clearance from organ sites, including lung, liver, kidney, gut and brain (Brash et al 1988).…”
Section: Discussion Referencessupporting
confidence: 80%
“…12 Maintenance on water ad libitum for 24 hours did not change AVP levels, whereas infusion of normal saline increased them by over fourfold. There are two possible explanations for the increased AVP seen in the subtotally-nephrectomized saline-infused animals.…”
Section: Discussionmentioning
confidence: 91%